Numerical simulation and wind tunnel measurements on a tricycle wheel sub-system. (1st January 2013) - Driant, Thomas; Fellouah, Hachimi; Moreau, Stéphane; Desrochers, Alain; Remaki, Lakhdar
The drag of an isolated rotating wheel subsystem including its accessories (tyre, suspension, A-arms and fender) of a tricycle vehicle has been studied both numerically and experimentally. The objective of this study is to validate the numerical model developed in order to optimise a generic wheel subsystem through drag analysis. The CAD model of the wheel subsystem was created in CATIA-v5 and the numerical simulations were carried out using the Star CCM+ commercial CFD package. The resulting numerical model was validated experimentally by comparing with the drag and pressure coefficient measured in a large subsonic closed-loop wind tunnel. Different mesh topologies and turbulent models were tested. The final model developed shows less than 3% of drag discrepancy vs. experimental results. Two aerodynamic shapes of A-arms are then designed to perform drag reduction on the wheel subsystem. Numerical simulations show a significant drag reduction up to 20% compared with the original wheel subsystem.